PENERAPAN PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR DESA CIPELANG - Siti Nuril Ilmih; Widya Anggriana (Institut Madani Nusantara, 2023)
The purpose this research is to describe the impact of thematic learning toward grade I, III and IV students result study in Elementary school 01 Cipelang. The research methodology that used is a Quasy Eksperiment and research’s plan with Time Series Design. Population in this research which total is 22 students. Based on analysis result obtained pretest mean is 38.77, meanwhile posttest result obtained mean is 74.77. results of t test obtained tcount 19.42, meanwhile ttabelt tabel with df = 22 – 1 = 21 and significant level (α) = 0.05 is 2,080. Because tcount ≥ ttabel or 19.41 ≥ 2,080. Then, Ho pushed away and Ha accepted means significant means there were impact of thematic learning toward grade II student’s result study in Elementary school 01 Nanga Dedai. Then, analysed of effectivity of using thematic learning gained effect size’s price 1.74 with high category. Then, with observation by teacher in class, using thematic learning founded very good change from students, the changes are students be more confident, creative and sprit in study.